2021
DOI: 10.1021/acs.joc.1c01497
|View full text |Cite
|
Sign up to set email alerts
|

α-Keto Acids as Triggers and Partners for the Synthesis of Quinazolinones, Quinoxalinones, Benzooxazinones, and Benzothiazoles in Water

Abstract: A general and efficient method for the synthesis of quinazolinones, quinoxalinones, benzooxazinones, and benzothiazoles from the reactions of α-keto acids with 2-aminobenzamides, benzene-1,2-diamines, 2-aminophenols, and 2-aminobenzenethiols, respectively, is described. The reactions were conducted under catalyst-free conditions, using water as the sole solvent with no additive required, and successfully applied to the synthesis of sildenafil. More importantly, these reactions can be conducted on a mass scale,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 86 publications
0
20
0
Order By: Relevance
“…DCM (1 L) was added, and the free base of 21 was extracted into an organic layer that was dried over Na 2 SO 4 and concentrated by rotary evaporation. To the residue (∼100 mL) was added 300 mL of n-heptane, and the mixture was stirred for 1 h. The resulting precipitate was collected by filtration, and the filter cake was dried in a vacuum at 45 °C to afford 21 (78.50 g, 96%) as a white solid: mp 78−84 °C; 1 H NMR (500 MHz, DMSO-d 6 ) δ 7.50 (dd, J = 7.6, 1.8 Hz, 1H), 7.33 (ddd, J = 8.3, 7.4, 1.8 Hz, 1H), 7.05 (dd, J = 8.4, 1.0 Hz, 1H), 6.94 (td, J = 7.5, 1.1 Hz, 1H), 6.36 (s, 3H), 4.07 (q, J = 7.0 Hz, 2H), 1.34 (t, J = 6.9 Hz, 3H); 13…”
Section: -Ethoxybenzimidamide (21)mentioning
confidence: 99%
See 2 more Smart Citations
“…DCM (1 L) was added, and the free base of 21 was extracted into an organic layer that was dried over Na 2 SO 4 and concentrated by rotary evaporation. To the residue (∼100 mL) was added 300 mL of n-heptane, and the mixture was stirred for 1 h. The resulting precipitate was collected by filtration, and the filter cake was dried in a vacuum at 45 °C to afford 21 (78.50 g, 96%) as a white solid: mp 78−84 °C; 1 H NMR (500 MHz, DMSO-d 6 ) δ 7.50 (dd, J = 7.6, 1.8 Hz, 1H), 7.33 (ddd, J = 8.3, 7.4, 1.8 Hz, 1H), 7.05 (dd, J = 8.4, 1.0 Hz, 1H), 6.94 (td, J = 7.5, 1.1 Hz, 1H), 6.36 (s, 3H), 4.07 (q, J = 7.0 Hz, 2H), 1.34 (t, J = 6.9 Hz, 3H); 13…”
Section: -Ethoxybenzimidamide (21)mentioning
confidence: 99%
“…■ EXPERIMENTAL SECTION General Information. 1 H nuclear magnetic resonance (NMR) and 13 C{ 1 H} NMR spectra were recorded using Bruker 400, 500, and 600 Hz instruments. 1 H NMR data are presented as chemical shifts in parts per million, and multiplicities are denoted as follows: s, singlet; d, doublet; t, triplet; q, quartet; m, multiplet; br, broad.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is hoped that quinazoline compounds can be obtained by decarboxylation of α-keto acid and then reacted with cheap and readily available o -benzylamine under blue LED conditions. In addition, while there are many reports on the cyclization of o -substituted aniline with α-keto acids, 16 the reaction of ortho substituted benzylamines with α-keto acids is rarely reported. In 2021, Laha et al 17 reported the cyclization of 2-aminbenzylamine with arylglyoxylic acid in the presence of K 2 S 2 O 8 , which is used as a key reagent in the decarboxylation step.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] However, most of these methods require transition-metal 13,14 or acid-base catalysis, 15 with some even requiring toxic organic solvents 16 or high-temperature catalysis, 15 which make these approaches not green. There are also two syntheses of 3-substituted quinoxalin-2(1H)-one derivatives: the reaction of o-phenylenediamine with -phenylglyoxylic acid or a ketone ester with glyoxylic acid, [17][18][19][20] or functionalization of the C 3 position of the quinoxalin-2(1H)-one derivative. [21][22][23][24] In addition, when synthesizing benzoxazin-2-one derivatives with anti-tumor effects, [25][26][27] Pd or Cu catalysts, 28 volatile solvents, 28 or strong oxidants 29 may be used; however, a longer reaction time is generally required.…”
mentioning
confidence: 99%